A A RETROSPECTIVE LONG-TERM STUDY ON AGE AT MENARCHE AND MENSTRUAL CHARACTERISTICS IN 85 YOUNG WOMEN WITH TRANSFUSION-DEPENDENT Β-THALASSEMIA (TDT) BORN BETWEEN 1965 AND 1995 - Vincenzo De Sanctis; Salvatore Di Maio (Mediterranean Journal of Hematology and Infectious Diseases)
Summary. Background: Menarche is an important milestone in the reproductive life of a woman, and regular menstrual cycles reflect normal functioning of the hypothalamic-pituitary-ovarian axis, a vital sign of women’s general health. Aim of the study:We explored the age at menarche and the following menstrual cycles characteristics among 85 unmarried Transfusion-Dependent β-Thalassemia (TDT) women,borned between 1965 and 1995, in relation to iron chelation therapy (ICT) with desferrioxamine (DFO) and nutritional status, assessed by body mass index (BMI). Results: 53 adolescents who had begun ICT before the age of 10 years experienced menarche at 13,7 ± 1,6 years (mean ± DS), whereas 32 who begun treatment after 10 years experienced menarche at the significantly later age (15.5 ± 1.9 yrs; p: 0.001). At the age of menarche: BMI-Z score (n= 67, - 0,09 ±1) was inversely correlated with both age at starting ICT (r = - 0,39; p = 0001) and age at menarche ( - 0,45, p = 0,0001). Serum ferritin levels (SF) were significantly correlated with the age at starting chelation therapy (n = 79; r = 0,34; p = 0,022). In 56 TDT adolescents who developed secondary amenorrhea (SA), the SF levels were significantly higher (4,098 ± 1,907 ng/mL) compared to 23 TDT adolescents with regular menstrual cycles (2,913±782 ng/mL; p = 0,005). A nutritional status of "thinness" at menarche was associated to a lower prevalence of subsequent regular menstrual cycles and to a higher prevalence of early SA. Conclusion: An early ICT in TDT patients was associated to a normal "tempo" of pubertal onset and to a higher frequency of subsequent regular menstrual cycles. In TDT patients, who developed SA, a diagnosis of acquired central hypogonadism was made, mainly due to the chronic exposure to iron overload, however other potential causes linked to nutritional status, deficient levels of circulating nutrientsand the chronic disease itself cannot be excluded.